PHARMACOLOGICAL MECHANISMS OF DRUG ACTION: PRINCIPLES AND APPLICATIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Pharmacology is a fundamental discipline in medical science that studies the interactions between drugs and biological systems. This article explores the core principles of pharmacological mechanisms, including pharmacokinetics and pharmacodynamics. Special emphasis is placed on how drugs are absorbed, distributed, metabolized, and excreted, as well as their effects at the cellular and receptor levels. Understanding these mechanisms is essential for rational drug use, minimizing adverse effects, and optimizing therapeutic outcomes. This paper follows the IMRAD structure to provide a comprehensive scientific overview.